Effects of Latin dance on social physique anxiety and physical self-esteem among middle school girls in Shanghai, China - Liu, Xutao (2024)
Physical activity has been widely recognised as improving physical and psychological well-being among adolescents, with dance emerging as an engaging and culturally diverse option. The period of adolescence is particularly critical as it involves rapid physical and emotional changes, making it imperative to address both physical and psychosocial well-being to foster a healthy development trajectory. This study investigates the impact of Latin dance on social physique anxiety (social physique anxiety total score, negative evaluation, self-performance, and social comparison) and physical self-esteem (physical self-esteem total score, sport competence, physical conditioning, bodily attractiveness, physical strength, and physical self-worth) of middle school girls, an age group particularly susceptible to body image concerns and self-esteem issues. This study employed a single-group pre-test and post-test design, recruiting 51 female participants (Age: Mean=12.78, SD=0.54) from one middle school in Shanghai, China. The experimental group engaged in a 12-week Latin dance intervention consisting of two sessions per week. Quantitative data were collected through three measurement points: pre-test (before the intervention), post-test 1 (after 6 weeks), and post-test 2 (after 12 weeks). The Social Physique Anxiety Scale (SPAS) and the Children Youth Physical Self-perception Profile (CY-PSPP) questionnaires were used to measure middle school girls' social physique anxiety and physical self-esteem. Statistical analysis of the data incorporated One-way repeated measures ANOVA (Analysis of Variance) and Generalized Estimating Equations (GEE). At baseline, a significant proportion of the participants exhibited high levels of social physique anxiety (Mean: 39.078, SE=0.322) and low levels of physical self-esteem (Mean: 56.392, SE=0.741), indicating the necessity of interventions targeted at these issues. The results of this study showed that Latin dance intervention can significantly reduce the Social Physique Anxiety Total Score (SPATS), including Negative Evaluation (NE), Self-Performance (SP) and Social Comparison (SC) of middle school girls. The effect sizes for these changes were notably large, with a pronounced change observed in SP (d=1.69). In addition, Latin dance intervention can significantly improve the Physical Self-Esteem Total Score (PSETS) of middle school girls, including Sport Competence (SPC), Physical Conditioning (PC), Bodily Attractiveness (BA), Physical Strength (PS) and Physical Self-Worth (PSW), with the most significant change in PC (d=1.90). On the other hand, the results showed that after 6 weeks of Latin dance intervention, only SPC and BA had no significant differences in the experimental group, while NE, SP, SC, SPATS, PC, PS, PSW and PSETS all had significant differences. After 12 weeks of the Latin dance intervention, SPATS, NE, SP, SC, PSETS, SPC, PC, BA, PS, and PSW were significantly different. The results showed that the 12 weeks Latin dance intervention was more effective than the 6 weeks intervention. Furthermore, the intervention effectively reduced the proportion of participants with poor social physique anxiety and physical self-esteem, thereby validating the potential of Latin dance as a holistic intervention. The results of this study verified the effectiveness of Latin dance intervention in reducing social physique anxiety and improving the physical self-esteem of middle school girls for 12 weeks. Adolescent girls who learn Latin dance have less anxiety and improve their physical health and self-esteem. The incorporation of Latin dance programs within middle school physical education curricula presents a promising avenue to address psychological well-being in adolescents. Future research should consider conducting long-term follow-up assessments to evaluate the sustainability of the improvements observed in social physique anxiety and physical self-esteem. In addition, exploring the effects of various dance styles beyond Latin dance could broaden our understanding of the impact of dance on psychological well-being.